Comparing Student Activity and Outcomes in Problem Based Learning and Guided Inquiry on Atomic Structure - Freddy Tua Musa Panggabean; Elsaida Siboro (Jurnal Pendidikan Kimia FKIP Universitas Halu Oleo, 2025)
This research is motivated by the low activity and learning outcomes of students in atomic structure material at SMAN 7 Medan. This study aims to determine significant differences in student learning activities, student learning outcomes and the correlation between student activity and learning outcomes taught with the Problem Based Learning (PBL) and Guided Inquiry learning models on atomic structure material. The research method used is the true experiment method with a Pretest - Posttest Control Group research design. The subjects of the study were grade X students at SMAN 7 Medan who were selected randomly: PBL Class (X-1) and Guided Inquiry Class (X-2). Hypothesis testing was carried out with the help of SPPS Statistics Version 27 Windows with a significance level of 5% using the Independent Sample T-Test and Bivariate Pearson Correlation. The results showed that for experimental class I: the average activity was 85% and learning outcomes were 86.67. While the experimental class II had an average activity of 84% and learning outcomes were 85.56.  The N-Gain results obtained in this study in experimental class I were 81% and experiment II was 80% with high criteria, which means that the PBL and guided inquiry learning models are effective in improving student learning outcomes. And the correlation results obtained that there is a correlation between student learning activities and student learning outcomes.